The Role of AI-Based Chatbots in Improving Public Services in Government Services in the Digital Era - Ibnu Ubaedila (Worldwide Research Publishing, 2025)
The development of artificial intelligence (AI) technology has driven significant transformation in the public service sector, especially through the implementation of chatbots. Traditional public services often face obstacles in the form of response delays, limited human resources, and low efficiency of information distribution. AI-based chatbots come as innovative solutions that offer speed, accuracy, and service availability on an ongoing basis. This research aims to analyze the role of AI chatbots in improving the quality of public services in the digital era, as well as identify the challenges and accompanying policy implications. The focus of the research is directed at how chatbots can increase public satisfaction, shorten response times, and ensure the accuracy of the information conveyed. The research method used is a qualitative approach with literature review and secondary data analysis from survey results and previous research reports. Data were analyzed through descriptive and visualization techniques using bar charts, circles, and horizontal graphs to illustrate community satisfaction, information accuracy, response time, and implementation challenges. The results show that AI chatbots are able to accelerate public service response times up to 75% faster than manual services, with an information accuracy rate of up to 60% in the high category. The level of public satisfaction also tends to be positive, with the majority of respondents feeling satisfied to very satisfied. However, the main challenges still faced include data privacy issues, public trust, technical integration, and ethical-legal aspects. This research confirms that the implementation of chatbots requires holistic policy support in order to become a strategic instrument in digital public service reform